Efektivitas Pembelajaran Daring di Indonesia - Syahri Syahri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The outbreak of the coronavirus in Indonesia affects all aspects of life including aspects of education.Learning that all goes face-to-face is now converted into online learning. This online learning is carriedout using internet media and various platforms which are now widely spread in Indonesia. Onlinelearning is one alternative that can overcome the challenge. This study aims to determine theeffectiveness of online learning that emphasizes integration with the environment from various sourcesin terms of various aspects during the educational era 4.0. Using the method in the form of a metaanalysis of journals, through a variety of journals related to the research variables collected thenreviewed and drawn a conclusion. The results of the study show that online learning will be effective ifit applies an essential component of Laurillard which covers aspects of discourse, adaption, interactionand reflection.